Leptomeningeal Metastasis from Carcinoma Breast: A Case of Unknown to Known - Soman, Princy S; A, Hemalatha; R, Kalyani; V, Lakshmaiah (Annals of Pathology and Laboratory Medicine, 2021)
Leptomeningeal metastasis is known to occur as an initial presentation in solid tumors. The presentation of meningeal symptoms before the diagnosis of primary tumor is seen in 10-20% cases. Though the sophisticated radiological imaging is available, Cerebrospinal Fluid (CSF) analysis for tumor cells remains the gold standard method for diagnosis. Incidence of brain metastasis from primary carcinoma breast is about 3-8% only. We present a case of young female who presented with neurological symptoms and misdiagnosed as meningitis on Magnetic Resonance Imaging (MRI), but later after CSF analysis it was diagnosed as metastases from carcinoma breast.